Factors affecting the postoperative survival rate of obese Asian patients with endometrial cancer - Gao, Huiqiao; Lu, Qi; Zhang, Jianxin (Journal of obstetrics and gynaecology, 2025)
The objective of this study was to explore the factors that influence overall survival in obese patients with endometrial cancer (EC). The retrospective study included patients with EC who were treated between 2000 and April 2013. Subjects were divided into the following groups based on body mass index (BMI): non-obese (<24.0 kg/m ), overweight (24.0-28.0 kg/m ) and obese (>28.0 kg/m ). Survival data were estimated using Kaplan-Meier's curves and compared using log-rank statistics. A total of 280 cases were enrolled, including 22.5% in non-obese group, 42.9% in overweight group and 34.6% in obese group. Among different BMI groups, obese EC patients with diabetes have a lower survival rate ( = .041), and obese EC patients with menopause have a lower survival rate ( = .021). The survival rate of overweight EC patients was significantly reduced if vascular thrombus and lymph node metastasis were found during operation ( < .001). Our data suggest that the association of obese EC patients with menstrual status, diabetes and intraoperative vasculature embolus and lymph node metastasis significantly affects postoperative survival. In all subjects, the relevant factors were independent prognostic factors in patients with obese.